Phylogenetic relationships of actinacantha simon, gasteracantha sundevall, macracantha hasselt and thelacantha simon spiny orb-weavers (Araneae: Araneidae) in peninsular Malaysia - Tan, Ji; Chan, Zi Yang; Ong, Ching Ang; Yong, Hoi Sen (National University of Singapore, 2019)
Spiny orb-weavers of the genera Actinacantha, Gasteracantha, Macracantha, and Thelacantha are spiders with rigid abdomens and prominent spines that are mostly endemic to Asia. The taxonomy and phylogeny of these spiders are poorly studied due to their intraspecific morphological variations, the rarity of male specimens in collections and the lack of distinctive morphological characters in older descriptions. Therefore, this study has employed for the first time, a multigene approach using three mitochondrial (CO1, CO2 and 16S) and two nuclear-encoded (H3A and 18S) molecular markers to aid in the identification and phylogenetic reconstruction of these spiny orb-weavers collected from Peninsular Malaysia. The genus Gasteracantha as presently circumscribed is not monophyletic, with G. hasselti C. L. Koch, 1837 forming a lineage with A. globulata (Walckenaer, 1841) and M. arcuata (Fabricius, 1793). Our results also revealed two different morphotypes of G. diardi which are morphologically different from G. mengei (Keyserling, 1864). The epigynal structures of G. diardi (Lucas, 1835), G. hasselti, G. kuhli C. L. Koch, 1837, G. mengei, M. arcuata, and T. brevispina (Doleschall, 1857) are illustrated. The morphology of G. diardi and G. mengei is detailed for the first time. © National University of Singapore.